Dynamics of species composition of small non-volant mammals from the northern Cordillera Central of Colombia (2015)
On the basis of our recent fieldwork and historical records, we document the diversity of small non-volant mammals in the northern end of Cordillera Central of Colombia, an important region in the context of vertebrate biodiversity.